Evaluasi Pelaksanaan Praktikum Biologi di SMA Negeri di Klaten pada ditinjau dari Kualitas Laboratorium, Pengelolaan, dan Pelaksanaan Praktikum - Putri Agustina; Alanindra Saputra; Eva Khusnul Khotimah; Dwi Rohmahsari; Nunuk Sulistyanti (BIO-PEDAGOGI, 2019)
Practicum is one of the learning methods that cannot be separated from Biology learning. Practicum becomes a vehicle for training and developing science process skills and scientific attitudes of students. Practicum can run well if it is carried out in accordance with the standards of practicum implementation. This study aims to evaluate the implementation of Biology practicum in Polanharjo Klaten 1 High School covering laboratory quality, management, and the implementation of 2017/2018 Biology semester practicum. This research is a descriptive research. The parameters studied included the quality of the laboratory, management of the lab, and the implementation of the Biology lab. Data collection techniques are carried out by observation, documentation, and interviews. The results showed that: (1) the quality of the Biology laboratory was in the good category with a percentage of 66.5%; (2) Biology practicum management is included in the good category with a percentage of 63.75%; and (3) Biology practicum is included in the excellent category with a percentage of 95.23%.